2015
DOI: 10.1039/c5tc02509e
|View full text |Cite
|
Sign up to set email alerts
|

High LUMO energy pyrrolidinofullerenes as promising electron-acceptor materials for organic solar cells

Abstract: We report the synthesis and investigation of four novel pyrrolidinofullerenes bearing electron donating alkoxyphenyl substituents. Cyclic voltammetry studies revealed that the designed fullerene derivatives have reduced electron affinity compared to the conventional material [60]PCBM. The organic bulk heterojunction solar cells based on the pyrrolidinofullerenes and P3HT revealed impressive open-circuit voltages of 700-780 mV and enhanced light power conversion efficiencies with respect to the reference PCBM/P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 36 publications
2
20
0
Order By: Relevance
“…In contrast to PCBM, during the same temperature range, PyF5 exhibits a broad endothermic feature during the first heating run, implying it being a dominantly amorphous material. This is most likely because PyF5 is a mixture of two stereoisomers due to hindered nitrogen inversion . A melting peak was observed in the first heating scan of pristine FAP1, indicating the crystalline‐feature of FAP1.…”
Section: Photovoltaic Characteristics Of Ptb7‐th Based Organic Solar supporting
confidence: 68%
“…In contrast to PCBM, during the same temperature range, PyF5 exhibits a broad endothermic feature during the first heating run, implying it being a dominantly amorphous material. This is most likely because PyF5 is a mixture of two stereoisomers due to hindered nitrogen inversion . A melting peak was observed in the first heating scan of pristine FAP1, indicating the crystalline‐feature of FAP1.…”
Section: Photovoltaic Characteristics Of Ptb7‐th Based Organic Solar supporting
confidence: 68%
“…[23][24][25] The model compound [6,6]-phenyl C 61 butyric acid methyl ester (PCBM), aw idely adopted electron acceptori n bulk heterojunction (BHJ) solar cells, has ah igherL UMO level (À4.08 eV) than that of pristine C 60 (À4.20 eV), and the addition of asecond malonate unit, formingabisadduct, furtherincreasest he LUMO energy (À3.97 eV). [32] In the case of C 59 N, addition of the first malonate moiety decreases the LUMO energy by 0.06 eV,s pecifically from À3.89 eV for (C 59 N) 2 to À3.95 eV for monoadduct 2.T his is analogous to observations in previous studies, [6,7] with opposing trends being reported forC 60 monoadducts. Addition of the second malonate to C 59 Nf orming bisadduct( AE)-3 raises the LUMO level to À3.81 eV,0 .08 eV higher than that of the parent (C 59 N) 2 .A ll redox data for (C 59 N) 2 ,m onoadduct 2,a nd bisadduct( AE)-3 are collected in Ta ble S2 (Supporting Information).…”
Section: Resultssupporting
confidence: 85%
“…The redox properties of (AE)-3 were screened by cyclic voltammetry.B isadduct (AE)-3 exhibits one irreversible wave at À1.17 Va nd three quasi-reversible reduction waves at À1.29, À1.73, and À2.20 V vs. Fc + /Fc (Figure 5b), which are about 140, 140, and 40 mV more negative than those for monoadduct 2.N otably,t he C 59 N-centred reduction potentials of (AE)-3 appear at more negative values than those reported for C 60 bisadducts. [23][24][25]32] It is also known that for mono-andb is-cyclopropanateda dducts of C 60 the LUMO level tends to drift to highere nergies. [23][24][25] The model compound [6,6]-phenyl C 61 butyric acid methyl ester (PCBM), aw idely adopted electron acceptori n bulk heterojunction (BHJ) solar cells, has ah igherL UMO level (À4.08 eV) than that of pristine C 60 (À4.20 eV), and the addition of asecond malonate unit, formingabisadduct, furtherincreasest he LUMO energy (À3.97 eV).…”
Section: Resultsmentioning
confidence: 99%
“…Fig. 18 shows that use of a properly designed fullerene derivative instead of PCBM improves both open circuit voltage and efficiency of organic bulk heterojunction solar cells [131]. Methanofullerenes bearing cyclopropane ring on the fullerene cage might be not the optimal compounds for realization of the through-space electronic interactions between organic addends and the fullerene cage.…”
Section: Scheme 2 the Bis-cycloaddutcs (Called Bis-adducts Below)mentioning
confidence: 98%
“…[97] We succeeded in the preparation of 1',2',5'-trisubstituted pyrrolidinofullerenes bearing two aryl groups in the pyrrolidine ring (Fig. 19) [132].…”
Section: Scheme 2 the Bis-cycloaddutcs (Called Bis-adducts Below)mentioning
confidence: 99%